Association Of Elevated Blood Pressure With The Mortality In Patients Of Intracerebral Hemorrhage (Journal of Pharmaceutical Negative Results, 2023)
BackgroundIn case of brain hemorrhages, the blood pressure monitoring is the main determinant to know the outcome of cerebrovascular event and resulting complications like bleeding recurrence of bleeding or expansion of hematoma. Rise in blood pressure at time of presentation can be a predictor of mortality in patients of intracerebral hemorrhage. The aim of current study was to find out the association of elevated blood pressure with the early mortality in patients of intracerebral hemorrhage.Methods: A cross-sectional study was conducted at the Medicine department of Abbasi Shaheed Hospital, Karachi during May to October 2022. Blood pressure of all the patients were recorded at the time of admission by using sphygmomanometer in lying position. CT scan was done at the same Abbasi Shaheed hospital and comments of radiologist on CT scan was noted. The study participants were followed until they got discharge from the hospital, just to note the frequency of early mortality. Data was analyzed by using the Statistical Package for Social Science (SPSS) version 20. p-value less than 0.05 was considered as significant.Results:The mean age of the study participants was 69.7 ± 3.5 years while majority of them were male (78.6%). Out of total 280 patients of cerebrovascular event due to intracerebral hemorrhage, the 120 (42.9%) patients had early mortality. About 48.3% cases of diabetes mellitus were found with early mortality and the result was statistically significant. Intraventricular extension of intracerebral hemorrhage reported 46.6% frequency of early mortality. Comparing normal and elevated blood pressure, the frequency of early mortality was higher in the patients of elevated blood pressure, there was strong significant association between early mortality in cases of intracerebral hemorrhage and high blood pressure.Conclusion:It can be concluded that the frequency of early mortality was higher in the patients of elevated blood pressure and there was a strong significant association between elevated blood pressure and the early mortality in patients of intracerebral hemorrhage.